Sistem Informasi Inventaris Laboratorium Komputer SMP Swasta IT Ad Durrah - Hamidi, Muhammad (Pusdikra Publishing, 2023)
SMP Swasta IT Ad Durrah is one of the schools that is part of the Islamic Secondary School Network and has very important aset in the computer lab. Currently, inventory data entry is done by hand using a book's guidelines, which is likely to hinder work processes. A newly developed information system designed to address the issue that has arisen. The system's objective is to make the inventory check process easier for users. Analysis of requirements, system performance, code writing, testing, and implementation. A well-designed inventory information system can assist in inventory counting and provide accurate information. Two different approaches to the information system are used to ensure good results. The black box method of testing can demonstrate that the system operates smoothly in accordance with requirements. However, the study that was conducted using the System Usability Scale (SUS) method yielded a rata-rata score of 77,5, indicating that users are satisfied with the information system that has been implemented.